Rare case of calcium phosphate urolithiasis in 2-month-old feline (Research, Society and Development, 2021)
Urolithiasis is one of the most important diseases related and relevant to the lower urinary tract of cats. This study aimed to report a rare case of a pediatric feline patient diagnosed with calcium phosphate urolithiasis. Thus, a complete abdominal ultrasound was performed, which revealed the presence of a structure in the caudal region of the urinary bladder, occupying virtually 80% of the total bladder size, there was a small quantity of urine present, so collection for urinalysis. Consequently, the patient was referred for cystotomy for the removal of urolithiasis. During the surgical procedure, several microuroliths were observed, which were grouped together, forming a single object of irregular shape and yellowish color. Through mineralogical analysis was detected the presence of 100% hydroxylated calcium phosphate, traces of calcium oxalate monohydrate, and traces of amorphous organic matrix. The presence and total composition of calcium phosphate in feline uroliths is much unusual in adults, and to the Best of our knowledge there are no records of it in kittens. This disease in a pediatric patient hás never been known to the best of our knowledge. So, this case is rare one for the age of the patient and the composition of the urolithiasis diagnosed in her urinary bladder and because of her early age.